Assessment of anxiety symptoms with low social support and associated factors among men who have sex with men (MSM): A cross-sectional study - Yi-Wei Zhou; Jun Li; Chun-Yan Shan; Zu-Mu Zhou (PLoS ONE, 2025)
Objective This study aims to examine the levels of anxiety symptoms and perceived social support among the men who have sex with men (MSM) population, to assess the level of both anxiety and low social support, and associated factors in this population. Method The study used an Internet service platform for MSM between March and June 2024. Sociodemographic information, laboratory test data, and scores from the Generalized Anxiety Disorder scale (GAD-7), and Perceived Social Support Scale (PSSS) were collected among men who have sex with men (MSM). Decision tree model and binary logistic regression were used to analyze the factors associated with anxiety with low perceived social support. Results A total of 1070 MSM respondents were recruited, of whom 19.6% had anxiety symptoms, and 12.90% had low social support. The prevalence of anxiety symptoms was significantly higher among individuals with low social support (38.41%) than among those with medium or high social support (16.95%) (P < 0.001). Specifically, 4.95% of all respondents had both anxiety and low social support. Logistic regression analysis showed that employment status (P = 0.028), self-esteem (P < 0.001) and psychological resilience (P < 0.001) were significant factors associated with both anxiety symptoms and low social support in the MSM population. Furthermore, the decision tree model identified self-esteem and psychological resilience as key predictors of both anxiety and low social support in the MSM population (all P < 0.05). Conclusion Our study demonstrated that in the MSM population in China’s eastern region, the prevalence of both anxiety and low social support was relatively low. Employment status, self-esteem, and psychological resilience were identified as significantly correlated factors for them. To effectively reduce anxiety in this population, interventions should focus on enhancing these factors.